Selective Compensation Strategies for the 3-phase Cascaded Multilevel Active Power Filter using ANF-based Sequence Decoupling Scheme - Xu, Lin; Han, Yang; Pan, Jun-min; Chen, Chen; Yao, Gang; Zhou, Li-Dan (Elektronika ir Elektrotechnika, 2010)
A new control strategy for the 3-phase multilevel cascaded H-bridge (CHB) active power filter is presented. The selective compensation of load side reactive and harmonic components is adopted to reduce the current controller bandwidth. The adaptive notch filters (ANFs) are utilized at the d-axis and q-axis of the load side currents to extract the positive- and negative-sequence components of individual harmonic component. The theoretical derivations of the ANF-based sequence decoupling scheme is outlined, followed by the design issues of the current regulators and the dc-link voltage controllers. Simulation results under balanced and unbalanced load conditions with transient load disturbances are presented for verification. The validity of the proposed control scheme is validated by the simulation results. Ill. 10, bibl. 11 (in English; summaries in English, Russian and Lithuanian).